Foresight and Public Utility Regulation - Gort, Michael; Wall, Richard A. (Journal of Political Economy, 1988)
The paper develops a model that shows the effects of rational expectations, and of efficient markets, on public utility regulation. It is shown that the feedback from investor expectations to regulatory behavior, together with investor expectations that take account of this feedback, basically alters the consequences of regulatory decisions. The analysis examines the effects of a deviation between the allowed rate of return and the cost of capital, with both perfect and imperfect investor foresight. It also assesses the consequences of differing expected growth rates. Conclusions are drawn for the effects of regulatory decisions on resource misallocation and of regulatory lag on incentives.